Prevalence of mental disorders and related risk factors in refugees and asylum seekers in Campania - Giuliani, Luigi; Bucci, Paola; Bracalenti, Raffaele; Giordano, Giulia Maria; Conenna, Matteo; Corrivetti, Giulio; Palumbo, Davide; Dell’Acqua, Andrea; Piras, Federica; Storti, Giovanna; Abitudine, Verdiana; Di Lieto, Roberta; et al. (Frontiers in Psychiatry, 2024)
The increasing presence of refugees and asylum seekers determined significant social, economic, humanitarian and public health implications in host countries, including Italy. These populations are exposed to several potential stressful experiences which make them vulnerable to psychological distress. In fact, the majority of studies addressing the topic found a higher prevalence of mental disorders, especially post-traumatic stress disorder and major depressive disorder, in refugees and asylum seekers with respect to the general population. However, heterogeneous prevalence rates have been reported among studies, due to methodological factor as well as to the impact of a variety of risk factors. The present study aimed to assess the prevalence of the main psychiatric diagnoses in a large group of adult refugees and asylum seekers (N=303) in the reception centers of two provinces of the Campania region, as well as to investigate the impact of potential risk factors on the occurrence of psychiatric disorders. The diagnosis of psychiatric disorders and the identification of subjects at high risk to develop psychosis were carried out by means of structured diagnostic interviews. The following variables were explored as potential risk/protective factors to the occurrence of psychiatric disorders: socio-demographic variables, migration status (refugees/asylum seekers) and characteristics of the reception center, assessed by means of an ad-hoc questionnaire; cognitive indices assessed by using standardized neuropsychological tests; traumatic experiences and level of political terror in the country of origin, assessed by means of reliable and valid self-report questionnaires. At least one mental disorder was found in 29.7% of the sample. Most prevalent diagnoses were depressive disorders, anxiety disorders and PTSD. Women showed a higher prevalence of anxiety disorders, higher trauma levels, and came from more at-risk countries. Higher trauma levels, better cognitive abilities and unemployment and refugee status were associated to the presence of a current psychiatric disorder in the whole sample. Our findings showed a higher prevalence of depressive disorders and PTSD in the sample of refugees and asylum seekers with respect to the general population and highlighted the role of potential risk factors whose identification may guide the implementation of preventive strategies and early treatments in these people.